Rise of azithromycin resistance: a study on antibiotic resistance pattern in culture positive cases of typhoid fever in a tertiary hospital in Delhi - Gaba, Manish; Sharma, Srikant; Biswal, Indu (International Journal of Research in Medical Sciences, 2022)
Background: Typhoid fever is a public health problem with a high disease burden in India. The prevalence of multidrug resistance in typhoid has nearly doubled from 1999 to 2005. The resistance against Fluoroquinlones is very high due to indiscriminate use and an increased resistance against Azithromycin, one of the first line antibiotics used is being observed. This study will evaluate the current trend of antibiotic resistance among typhoid fever cases observed in a tertiary care hospital. Methods: A retrospective record-based analysis was carried out for all the culture-proven typhoid cases admitted to a tertiary care teaching hospital in Delhi. The blood culture reports of all patients admitted from 1 January 2016 to 31 December 2017 were analyzed. Only culture-positive typhoid fever cases which isolated S. typhi and S. Paratyphi A were included for the study. The antibiotic sensitivity pattern was done using disc diffusion method and data with regards to following antibiotics was analysed: Azithromycin, ciprofloxacins, Amikacin, Gentamycin, Amoxicillin, Cefepime, Cefixime, Cotrimoxazole, Ceftriaxone. Results: The incidence of blood culture positive typhoid among total number of blood cultures received was 1.84%. Of these 118 blood cultures, 101 (85.6%) were S. typhi, and 17 (14.4%) were S. Paratyphi A. A total of 54 (45.8%) blood cultures were sensitive to all antibiotics. The antibiotic sensitivity testing revealed the following pattern of resistance: Azithromycin (21.2%), ciprofloxacin (16.9%), Gentamycin (10.2%), Amoxicillin (8.5%), Cefepime (1.7%), Cefixime (4%), Cotrimoxazole (4.2%), Ceftriaxone (0.8%). Conclusions: There is an increase in the resistance against Azithromycin in the typhoid bacilli. A regular and yearly assessment of antibiotic sensitivity pattern should be undertaken by developing a registry that accumulates antibiotic resistance data from hospitals and diagnostic centers.